2019
DOI: 10.2337/dc18-2315
|View full text |Cite
|
Sign up to set email alerts
|

Gluten Intake and Risk of Islet Autoimmunity and Progression to Type 1 Diabetes in Children at Increased Risk of the Disease: The Diabetes Autoimmunity Study in the Young (DAISY)

Abstract: To study the association of gluten intake with development of islet autoimmunity and progression to type 1 diabetes. RESEARCH DESIGN AND METHODSThe Diabetes Autoimmunity Study in the Young (DAISY) follows children with an increased risk of type 1 diabetes. Blood samples were collected at 9, 15, and 24 months of age, and annually thereafter. Islet autoimmunity was defined by the appearance of at least one autoantibody against insulin, IA2, GAD, or ZnT8 (zinc transporter 8) in at least two consecutive blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 37 publications
1
39
3
Order By: Relevance
“…Of note, both the exposure (intake of gluten-containing cereals rather than amount of gluten) and outcome was different from our study, and the number of children with outcome was small in these high-risk cohorts. A recent study of high-risk children found that an increased gluten intake in childhood was associated with islet autoimmunity but not with type 1 diabetes [28], while another study of high-risk children found no significant association between the child's gluten intake and islet autoimmunity or progression from islet autoimmunity to type 1 diabetes [29]. Again, the apparent inconsistency may have been due to studies investigating different outcomes (clinical type 1 diabetes versus progression) in different populations or due to lack of power.…”
Section: Comparison With Previous Studiesmentioning
confidence: 96%
“…Of note, both the exposure (intake of gluten-containing cereals rather than amount of gluten) and outcome was different from our study, and the number of children with outcome was small in these high-risk cohorts. A recent study of high-risk children found that an increased gluten intake in childhood was associated with islet autoimmunity but not with type 1 diabetes [28], while another study of high-risk children found no significant association between the child's gluten intake and islet autoimmunity or progression from islet autoimmunity to type 1 diabetes [29]. Again, the apparent inconsistency may have been due to studies investigating different outcomes (clinical type 1 diabetes versus progression) in different populations or due to lack of power.…”
Section: Comparison With Previous Studiesmentioning
confidence: 96%
“…Based on face‐to‐face interactions and validated questionnaires (food frequency and youth adolescent questionnaires), the age of starting gluten and the quantity of intake was analyzed. At the end of follow‐up at a median age of 13.5 years, 178 children had developed islet autoimmunity and 56 children had progressed to T1D . That study could find no association between gluten intake between 1 and 2 years of age or quantity of intake and onset of islet autoimmunity or progression to T1D.…”
Section: Can T1d Be Prevented By Going Gluten Free?mentioning
confidence: 91%
“…A recent publication from Diabetes Care in January 2019 titled Gluten Intake and Risk of Islet Autoimmunity and Progression to Type 1 Diabetes in Children at Increased Risk of the Disease: The Diabetes Autoimmunity Study in the Young (DAISY) discusses this topic . That study, conducted in Denver, Colorado, follows children at risk of diabetes based on diabetes‐susceptibility alleles in the human leukocyte antigen (HLA) region tested from cord blood as well as unaffected children with first‐degree relatives with T1D.…”
Section: Can T1d Be Prevented By Going Gluten Free?mentioning
confidence: 99%
“…The nutrition Consensus Report ( 1 ) and four featured papers ( 2 5 ) in the special section on nutrition in this issue of Diabetes Care focus on nutrition therapy and medical nutrition therapy (MNT) in the management and prevention of diabetes. The Consensus Report, which is intended to update and replace the 2014 American Diabetes Association (ADA) nutrition position statement ( 6 ), examines “studies published in English between 1 January 2014 and 28 February 2018” to “provide clinical professionals with evidence-based guidance” ( 1 ) related to the 42 questions listed in Table 1 .…”
mentioning
confidence: 99%
“…The role of gluten (a storage protein found in wheat, rye, and barley) in the etiology of diabetes remains controversial. In an observational analysis of children at high risk for type 1 diabetes published in this issue of Diabetes Care , intake of gluten at age 1–2 years was not associated with development of islet autoimmunity or progression to type 1 diabetes ( 2 ). Likewise, among individuals without diabetes, lower gluten intake was not associated with reduced risk of developing type 2 diabetes ( 13 ).…”
mentioning
confidence: 99%